2013
DOI: 10.5624/isd.2013.43.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of panoramic radiography with cone beam CT in predicting the relationship of the mandibular third molar roots to the alveolar canal

Abstract: PurposePreoperative radiographic assessment of the mandibular third molars is essential to prevent inferior alveolar nerve damage during extraction. The purpose of this study was to assess the reliability of panoramic signs of association between the roots of teeth and the canal, and to compare the panoramic signs with cone beam computed tomography (CBCT) findings.Materials and MethodsCBCT images of 132 impacted mandibular third molars were evaluated to determine the association of the root to the canal. The C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 15 publications
2
30
0
1
Order By: Relevance
“…Although panoramic images cannot provide three-dimensional information, numerous clinical studies [ 2 , 5 , 7 , 11 -13, 17 ] have been performed to determine panoramic findings suggestive of inferior alveolar nerve exposure or postoperative dysesthesia. In addition, many studies reported the panoramic findings that associated direct contact between inferior alveolar nerve and impacted third molar on computed tomography or cone-beam CT images [ 8 , 14 , 18 ]. In the present study, the most frequent panoramic radiographic finding was interruption of mandibular canal (69.14%), in conformity with previously published studies [ 2 - 4 , 6 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although panoramic images cannot provide three-dimensional information, numerous clinical studies [ 2 , 5 , 7 , 11 -13, 17 ] have been performed to determine panoramic findings suggestive of inferior alveolar nerve exposure or postoperative dysesthesia. In addition, many studies reported the panoramic findings that associated direct contact between inferior alveolar nerve and impacted third molar on computed tomography or cone-beam CT images [ 8 , 14 , 18 ]. In the present study, the most frequent panoramic radiographic finding was interruption of mandibular canal (69.14%), in conformity with previously published studies [ 2 - 4 , 6 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In oral and maxillofacial surgery practice, OPG is the most widely used technique for evaluating the lower third molar position and its relationship with the IAN canal 6 . Several clinical studies have determined specific radiographic signs, such as darkening of the root, narrowing or diversion of the IAN canal and interruption of the superior cortical line of the IAN canal wall, being highly suggestive of the close proximity between the lower third molars and the IAN canal 1 , 2 , 3 , 6 , 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, it was found that interruption of the radiopaque borders of the canal in PAN images predicted a direct contact between the roots of the third molar and the mandibular canal observed in CBCT 45,49-52 ( Figure 1), and in other studies, it was found that darkening of the roots in PAN images predicted a direct contact between the roots of the third molar and the mandibular canal observed in CBCT. 48,50,52,53 In one of the studies darkening of the roots was present in 5 of 43 of the PAN images, and the absence of cortication between the third molar and the mandibular canal was present in 33 of 43 of CBCT images. 48 The 5 cases were interpreted with no bony separation in the CBCT images, on the other hand, 28 cases were also determined with no bony separation in the CBCT images, and therefore, the agreement between the presence of darkening of the roots in the PAN images and the absence of bone between the tooth and the mandibular canal was only 15.2%.…”
Section: Level 2-effect On Diagnostic Accuracymentioning
confidence: 93%